The Effect of Private Antitrust Litigation on the Stock-Market Valuation of the Firm - Bizjak, John M.; Coles, Jeffrey L. (American Economic Review, 1995)
We study the implications for shareholder wealth of interfirm antitrust litigation and how the costs of the dispute affect the propensity to settle. Upon filing, defendants experience significant wealth losses that are ten million dollars larger than the wealth gains of plaintiffs. Financial distress, behavioral constraints, and follow-on suits are sources of wealth leakage and influence settlement behavior. Since the threat of a monetary transfer has little power to explain either wealth effects or the likelihood of settlement, the central concern of defendants may be the potential prohibition of profitable business practices.